Clinical Trials for Gene Therapy in Lysosomal Diseases With CNS Involvement - Sevin, Caroline; Deiva, Kumaran (Frontiers in Molecular Biosciences, 2021)
Abstract There are over 70 known Lysosomal Storage Disorders (LSDs), the majority of them caused by mutations in genes encoding lysosomal hydrolases. Central nervous system (CNS) involvement is a hallmark of the majority of LSDs and most often makes the prognosis of the disease, if present. However, brain disease is currently poorly targeted by available therapies, including systemic enzyme replacement therapy (ERT), mostly (but not only) due to the presence of the blood-brain barrier (BBB) that preclude the access of oral or parenteral large molecules into the brain. Thus, one of the greatest and exciting challenge of the next years will be to succeed in developing effective therapies for the treatment of CNS manifestations in LSDs. Over the past years, gene therapy (GT) has emerged as a promising therapeutic strategy for a variety of inherited neurodegenerative diseases. In LSDs, the ability of genetically corrected cells to cross-correct adjacent deficient cells into the brain after gene transfer may enhance the diffusion of the recombinant enzyme, making this group of diseases a strong candidate for such an approach. Both in vivo (using administration of recombinant adeno-associated viral vectors) or ex vivo strategies (auto-transplantation of lentiviral vector-modified hematopoietic stem cells - HSCs) are achievable. Promising results were obtained in an ever-increasing number of preclinical studies in rodents and large animal models of LSDs, that gave a great hope of success for GT to correct the neurological defects, once translated to the clinics. We are now at this stage of treating patients and several clinical trials are in progress, to assess the safety and efficacy of in vivo and ex vivo GT in several neuropathic LSDs. In this review, we will summarize the different approaches, review the current clinical trials available for neuropathic LSDs, their results (if any) and their limits. We will also try to evaluate the pitfalls and the remaining challenges to overcome.